Athens and Attica in prehistory : proceedings of the International Conference, Athens, 27-31 May 2015 - Papadimitriou, Nikolas,; Wright, James C., 1946-; Fachard, Sylvian,; Polychronakou-Sgouritsa, Naya,; Andrikou, Eleni, (Archaeopress Archaeology, 2020)
This resource provides the most complete overview of the Attica region from the Neolithic to the end of the Late Bronze Age. It paves the way for a new understanding of Attica in the Early Iron Age and indirectly throws new light on the origins of what will later become the polis of the Athenians.